2015
DOI: 10.1016/j.envres.2015.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity evaluation of new agricultural fungicides in primary cultured cortical neurons

Abstract: Fungicides are crucial for food protection as well as for the production of crops of suitable quality and quantity to provide a viable economic return. Like other pesticides, fungicides are widely sprayed on agricultural land, especially in wine-growing areas, from where they can move-off after application. Furthermore, residues of these agrochemicals can remain on crops after harvest and even after some food processing operations, being a major exposure pathway. Although a relatively low toxicity has been cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 30 publications
3
25
0
2
Order By: Relevance
“…Interestingly, a meta-analysis included in the paper found pyraclostrobin and azoxystrobin to have the highest risk quotients. Other studies highlighted the potential for these chemicals to cause neurotoxicity in vitro [8,9]. In addition, pyraclostrobin has been demonstrated to stimulate mitochondrial dysfunction and adipogenic activity in human cell lines [10,11]; however, effects by other strobilurins have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a meta-analysis included in the paper found pyraclostrobin and azoxystrobin to have the highest risk quotients. Other studies highlighted the potential for these chemicals to cause neurotoxicity in vitro [8,9]. In addition, pyraclostrobin has been demonstrated to stimulate mitochondrial dysfunction and adipogenic activity in human cell lines [10,11]; however, effects by other strobilurins have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…This class of fungicide, developed in the 1990s has rapidly become the second most prevalent type of fungicide, accounting for a $600 million industry that includes treatment of soybean, wheat and other cereal crops. Compounds like kresoxim-methyl and pyraclostrobin are broad-spectrum fungicides that have long-term stability [19] and were recently shown to be neurotoxic to cultured mammalian neurons [20]. Pyraclostrobin fed to rodents was also associated with stomach ulcerations, reduced weight gain and decreased food consumption [21].…”
Section: Strobilurinsmentioning
confidence: 99%
“…To date, most studies were focused on the field effectiveness of metrafenone (Capriotti, Gentili, Vecchio, Balzaretti, & Fagnani, 2006;Felsenstein, Semar, & Stammler, 2010;Opalski et al, 2006;Regueiro, Olguin, Simal-Gandara, & Sunol, 2015). Same effects regarding of metrafenone applied to vines on the color, fermentation, aroma and so on were reported (Briz-Cid, FigueiredoGonzalez, Rial-otero, Cancho-Grande, & Simal-Gandara, 2014;Noguerol-Pato, Sieiro-Sampredro, Gonzalez-Barreiro, CanchoGrande, & Simal-Gandara, 2014;Noguerol-Pato, Torrado-Agrasar, Gonzalez-Barreiro, Cancho-Grande, & Simal-Gandara, 2014), the results showed that metrafenone could produce an increase in the ripe fruit odorant series and higher biomass.…”
Section: Introductionmentioning
confidence: 99%